2013
DOI: 10.7314/apjcp.2013.14.10.5675
|View full text |Cite
|
Sign up to set email alerts
|

Expression Characteristics of Proteins of the Insulin-like Growth Factor Axis in Non-small Cell Lung Cancer Patients with Preexisting Type 2 Diabetes Mellitus

Abstract: Background: Preexisting type 2 diabetes mellitus (T2DM) affects the prognosis and mortality of patients with some cancers. Insulin like growth factor (IGF) and insulin receptor (IR) signaling axes play important roles in both cancer and diabetes development. We aimed to explore the expression characteristics of proteins in IGF/IR axis in non-small cell lung cancer (NSCLC) cases with preexisting T2DM. Methods: Fifty-five NSCLC patients with preexisting T2DM were retrospectively included and matched by 55 NSCLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…It was demonstrated that addition of anti-IGF1R treatment to paclitaxelcarboplatin combination therapy in NSCLC improved the response to treatment (Gualberto and Karp, 2009;Karp et al, 2009;Goto et al, 2012;Chen et al, 2013). Studies have shown that there could be a correlation between K-Ras status and IGF1R expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that addition of anti-IGF1R treatment to paclitaxelcarboplatin combination therapy in NSCLC improved the response to treatment (Gualberto and Karp, 2009;Karp et al, 2009;Goto et al, 2012;Chen et al, 2013). Studies have shown that there could be a correlation between K-Ras status and IGF1R expression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that IGF1R plays an important role in the development and progression of many cancers such as prostate, breast, liver, and colorectal cancers and brain tumors (Resnik et al,1998;O'Brien et al, 2001;Alexia et al, 2004;Samani et al, 2007;Xiong et al, 2012;Li et al, 2013). Even though studies performed to assess the role of IGF1R in lung cancer have given conflicting results, the common outcome of the studies is that IGF1R may be an autocrine growth factor for lung cancer (Ding et al, 2013;Vincent et al, 2013). The purpose of this study was to determine whether IGF1R expression evaluated by an immunohistochemical method would have a prognostic role in non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 95%
“…Hyperglycemia make available energy for malignant cell production and, via the peculiar energy utilization of cancer cells, favors cancer growth and neoangiogenesis (Ding et al, 2013). Also high serum glucose shows the way to swift augmentation of insulin from the pancreatic beta cells, and elevated insulin levels can be allied with insulin resistance.…”
Section: Role Of Hyperinsulinemia In Increased Risk Of Prostate Cancementioning
confidence: 99%
“…Despite advances in early diagnosis and treatment modalities, prognosis remains poor; the five-year survival rate is only about 15% (Mulshine et al, 2005). Individuals at risk for developing lung cancer can be identified by clinical epidemiologic factors (Bach et al, 2003;Spitz et al, 2007;Cassidy et al, 2008;Tammemagi et al, 2011;Ding et al, 2013) and it has been well established that tobacco smoking is the most important cause of lung cancer, accounting for 85%-90% of all cases in the world (Ruano-Ravina et al, 2003;Tyczynski et al, 2003). The remaining cases were attributable to nonsmoking causes such as pulmonary tuberculosis, environmental exposure to radon and arsenic in drinking water in homes, occupational exposure to asbestos and other carcinogens, as well as family history of lung cancer (Lam et al, 2004; RESEARCH ARTICLE Bruske-Hohlfeld, 2009;Gao et al, 2009;WU et al, 2011).…”
Section: Introductionmentioning
confidence: 99%